User Interface for the SMAC Traffic Accident Reconstruction Program - Krulec, Rok; Batista, Milan (Promet - Traffic&Transportation, 2003)
This paper describes the development of the user interfacefor the traffic accident reconstruction program SMAC. Threebasic modules of software will be presented. Initial parametersinput and visualization, using graphics library for simulation of3D space, which form a graphical user interface, will be explainedin more detail. The modules have been developed usingdifferent technologies and programming approaches to increaseflexibility in further development and to take maximumadvantage of the currently accessible computer hardware, sothat module to module communication is also mentioned.